2020
DOI: 10.3389/fpsyg.2019.03059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Interactive Use of Performance Measurement Systems on Job Performance: Mediation Effect of Organizational Learning

Abstract: Interactive controls that focus on communication and continuous learning are very important to achieve a competitive advantage. To better understand the underlying mechanism of how performance measurement systems (PMSs) improve job performance, a mediation model was constructed in the current study to examine organizational learning as a possible mediating variable. Data were collected using a questionnaire in China with a sample size of 191 managers. Structural equation model and Smart-PLS methods were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
(62 reference statements)
1
8
0
1
Order By: Relevance
“…Firstly, it aggregates new evidence of using the PMS relative to organizational learning. It corroborates previous studies that found a positive relationship between the interactive use of MCSs and learning (Henri, 2006;Srimai et al, 2011;Zhang & Yu, 2020) and, regarding the diagnostic use, it supports the perspective of a positive effect (Oyadomari et al, 2013) in contrast to the negative effect (Henri, 2006). Secondly, beyond the discussion that organizational learning promotes innovation (Huber, 1998), it extends the discussion to different levels of novelty in creativity: improvisational and compositional (Valaei et al, 2017).…”
Section: Implications and Contributionssupporting
confidence: 88%
See 3 more Smart Citations
“…Firstly, it aggregates new evidence of using the PMS relative to organizational learning. It corroborates previous studies that found a positive relationship between the interactive use of MCSs and learning (Henri, 2006;Srimai et al, 2011;Zhang & Yu, 2020) and, regarding the diagnostic use, it supports the perspective of a positive effect (Oyadomari et al, 2013) in contrast to the negative effect (Henri, 2006). Secondly, beyond the discussion that organizational learning promotes innovation (Huber, 1998), it extends the discussion to different levels of novelty in creativity: improvisational and compositional (Valaei et al, 2017).…”
Section: Implications and Contributionssupporting
confidence: 88%
“…H1a and H1b predict that the diagnostic and interactive use of the PMS positively influences organizational learning, with both being supported statistically and presenting small to medium effect sizes. This finding contrasts with the positive effect of the interactive use of the PMS or other MCSs on organizational learning (Henri, 2006;Srimai et al, 2011;Zhang & Yu, 2020). Moreover, it aggregates new evidence related to the diagnostic use of the PMS and its relationship with organizational learning since the literature indicates negative effects (Henri, 2006) and positive effects (Oyadomari et al, 2013).…”
Section: Discussion Of Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Prescriptive learning is experiential learning where information is acquired from employees' knowledge and experience, and is later transformed into a viable idea. In gaining experience, some persons perceive information through concrete, tangible and immersed reality [11]. Other persons acquire new information by conceptualization, i.e., analyzing and thinking through rather than using sensation.…”
Section: Prescriptive Learningmentioning
confidence: 99%